Australian National Enterovirus Reference Laboratory annual report, 2023 - Kaye, Matthew B; Hobday, Linda K; Ibrahim, Aishah; Bruggink, Leesa; Thorley, Bruce R (Communicable Diseases Intelligence, 2025)
Australia monitors its polio-free status by conducting surveillance for cases of acute flaccid paralysis (AFP) in children less than 15 years of age, as recommended by the World Health Organization (WHO). Cases of AFP in children are notified to the Australian Paediatric Surveillance Unit or the Paediatric Active Enhanced Disease Surveillance System and faecal specimens are referred for virological investigation to the National Enterovirus Reference Laboratory. In 2023, no cases of poliomyelitis were reported from clinical surveillance and Australia reported 1.71 non-polio AFP cases per 100,000 children, thereby meeting the WHO’s performance criterion for a sensitive surveillance system. The non-polio enteroviruses coxsackievirus A9, coxsackievirus B5, echovirus 9, echovirus 30, enterovirus A71 and enterovirus C96 were identified from clinical specimens collected from AFP cases. Australia also performs enterovirus and wastewater surveillance to complement the clinical system focussed on children. In 2023, there were twelve cases of wild poliovirus reported from the last two remaining endemic countries: Afghanistan and Pakistan. Another 23 countries reported cases of poliomyelitis due to circulating vaccine-derived poliovirus.